A Well Regulated Militia Political and Military Organisation in Pre-Napoleonic Switzerland (1550-1799) - Gassmann Jürg (Acta Periodica Duellatorum)
The period sees the transition of the ordinary fighter from feudal levy, yeoman or city burgher militia, to subject in an absolute polity, to today’s concept of the free citizen in a democratic state. In the period, the Swiss Confederacy was the only major polity that was not monarchical, but republican, and at the same time eschewed a standing army in favour of continued reliance on militia throughout.